Uncommon opportunities for achieving sustainable food and nutrition security: an agenda for science and public policy - International Food Policy Research Institute (International Food Policy Research Institute, 1996)
This brief addresses the need to harness science and technology for the transformation of agriculture into a primary instrument of a global Evergreen Revolution. Based on the principles of ecology, social equity, energy efficiency, employment generation, and economic viability, this revolution will provide the technical foundation for the universal eradication of hunger and the achievement of a food- and nutrition-secure world for all. At the same time, it emphasizes the urgent need for adoption, particularly by developing countries, of population policies that can ensure that children are born with a chance for happiness and not for mere existence. It describes a new revolution in agriculture and outlines a scientific and public policy agenda for sustainable food and nutrition security. Finally, it addresses the role of the international community in this effort.